KOLABORASI UNTUK PERUBAHAN: STRATEGI SOSIALISASI NAPZA DALAM MEMBANGUN KESADARAN DAN KEPEDULIAN BERSAMA - Ngatoillah Linnaja; Sriana Dewi; Vena Artiani; Auliya sholikhatun; Az Zahra Agni Saqinna; Putri Ayu Kusuma Wardani; Awalia Putri Sofiya; Ayu Saputri; Eka nur wiidyanti; Stefi Gilang Ramadani; Muhamad Bayu Akbar; Achmad lutfi sujadi; Ahmad Sahal Mahfudz; Bima Kurniawam Sutikno (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The abuse of Narcotics, Psychotropic Substances, and Addictive Substances (NAPZA) is an escalating social issue in Indonesia, particularly among adolescents and university students. This has serious implications for the health, social, and economic aspects of society. This research aims to analyze the strategy of NAPZA socialization in Dusun Gintung, Desa Ngadimulyo District, Temanggung Regency, and the effectiveness of multi-party collaboration in raising awareness and fostering community concern about the dangers of NAPZA. The method used is a descriptive qualitative approach, involving various parties such as the village government, police, health professionals, and schools. The findings show that NAPZA socialization through interactive lectures, group discussions, and the use of social media has successfully raised community awareness, although challenges in changing the mindset of some residents remain. The role of the youth as agents of change through the